Measurement of Cell Adhesion and Migration Using Phosphor-Screen Autoradiography. (August 1996) - Dalton, B.A.; Dziegielewski, M.; Johnson, G.; Underwood, P.A.; Steele, J.G.
This study demonstrates the use of phosphor-screen autoradiography as a means of measuring cell adhesion and cell expansion on polymer surfaces. The method has particular merit in cases where a specific substrate may be opaque or biochemically incompatible with colorimetric assay methodologies. With the phosphor-screen autoradiography method, there was a linear relationship between cell number and quantitated radioactivity. The technique has also been validated by comparison with a colorimetric assay of adhesion conducted for attachment to conventional culture substrata. The data supported the view that the use of phosphor-screen autoradiography was a valid method for detecting cell attachment, and it gave equivalent results to the colorimetric assay. Furthermore, a comparison between phosphor-screen autoradiography and a dye-staining method showed that this technique can be used as a means of quantifying cellular expansion over surfaces.